1999
DOI: 10.1091/mbc.10.10.3187
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Administration of Gangliosides Displaces GPI-anchored Proteins from Lipid Microdomains in Living Cells

Abstract: Exogenous application of gangliosides to cells affects many cellular functions. We asked whether these effects could be attributed to the influence of gangliosides on the properties of sphingolipid-cholesterol microdomains on the plasma membrane, also termed rafts. The latter are envisaged as lateral assemblies of sphingolipids (including gangliosides), cholesterol, and a specific set of proteins. Rafts have been implicated in processes such as membrane trafficking, signal transduction, and cell adhesion. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 41 publications
3
73
0
1
Order By: Relevance
“…Although clustering of lipid raft components can be disrupted by altering levels of various raft components (Varma and Mayor, 1998;Simons et al, 1999), it seems unlikely that such an effect occurs in our experiments, which were performed using endogenous markers for rafts. We obtained a similar, density-dependent energy transfer for both endogenous (this study) and transfected (Kenworthy and Edidin, 1998) GPI-anchored proteins, indicating that these molecules had not been artificially dispersed from a clustered distribution because of saturation of the available raft lipids or competition for enrichment in a limited number of clusters.…”
Section: Discussionmentioning
confidence: 92%
“…Although clustering of lipid raft components can be disrupted by altering levels of various raft components (Varma and Mayor, 1998;Simons et al, 1999), it seems unlikely that such an effect occurs in our experiments, which were performed using endogenous markers for rafts. We obtained a similar, density-dependent energy transfer for both endogenous (this study) and transfected (Kenworthy and Edidin, 1998) GPI-anchored proteins, indicating that these molecules had not been artificially dispersed from a clustered distribution because of saturation of the available raft lipids or competition for enrichment in a limited number of clusters.…”
Section: Discussionmentioning
confidence: 92%
“…It is also possible that GM1 alters raft-like domain structure, reducing Thy-1 partitioning into them. Indeed, a recent study has shown that increased levels of GM1 displace GPI-anchored proteins from sphingolipidcholesterol microdomains in living cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that carbohydrate moiety of GSLs can affect the interaction of TAG-1 with lipid rafts or the physical properties of lipid rafts. A recent report showed that exogenously administered ganglioside, which was incorporated in lipid raft fraction, displaced GPI-anchored proteins from lipid rafts and increased their detergent solubility (77,78). This finding suggests that GSL can affect distribution of GPI-anchored proteins in lipid rafts.…”
Section: Role Of Gsl In Gpi-anchored Protein Signaling In Lipidmentioning
confidence: 95%